Palmitoylation of LIM Kinase-1 ensures spine-specific actin polymerization and morphological plasticity - George, Joju (eLife, 2015)
Precise regulation of the dendritic spine actin cytoskeleton is critical for neurodevelopment and neuronal plasticity, but how neurons spatially control actin dynamics is not well defined. Here, we identify direct palmitoylation of the actin regulator LIM kinase-1 (LIMK1) as a novel mechanism to control spine-specific actin dynamics. A conserved palmitoyl-motif is necessary and sufficient to target LIMK1 to spines and to anchor LIMK1 in spines. ShRNA knockdown/rescue experiments reveal that LIMK1 palmitoylation is essential for normal spine actin polymerization, for spine-specific structural plasticity and for long-term spine stability. Palmitoylation is critical for LIMK1 function because this modification not only controls LIMK1 targeting, but is also essential for LIMK1 activation by its membrane-localized upstream activator PAK. These novel roles for palmitoylation in the spatial control of actin dynamics and kinase signaling provide new insights into structural plasticity mechanisms and strengthen links between dendritic spine impairments and neuropathological conditions. DOI: http://dx.doi.org/10.7554/eLife.06327.001